Description of a Large Family with Autosomal Dominant Hypercholesterolemia Associated with the APOE p.Leu167del Mutation. Issue 1 (11th October 2012) - Marduel, Marie; Ouguerram, Khadija; Serre, Valérie; Bonnefont‐Rousselot, Dominique; Marques‐Pinheiro, Alice; Erik Berge, Knut; Devillers, Martine; Luc, Gérald; Lecerf, Jean‐Michel; Tosolini, Laurent; Erlich, Danièle; Peloso, Gina M.; et al.
ABSTRACT Apolipoprotein (apo) E mutants are associated with type III hyperlipoproteinemia characterized by high cholesterol and triglycerides levels. Autosomal dominant hypercholesterolemia (ADH), due to the mutations in the LDLR, APOB, or PCSK9 genes, is characterized by an isolated elevation of cholesterol due to the high levels of low‐density lipoproteins (LDLs). We now report an exceptionally large family including 14 members with ADH. Through genome‐wide mapping, analysis of regional/functional candidate genes, and whole exome sequencing, we identified a mutation in the APOE gene, c.500_502delTCC/p.Leu167del, previously reported associated with sea‐blue histiocytosis and familial combined hyperlipidemia. We confirmed the involvement of the APOE p.Leu167del in ADH, with (1) a predicted destabilization of an alpha‐helix in the binding domain, (2) a decreased apo E level in LDLs, and (3) a decreased catabolism of LDLs. Our results show that mutations in the APOE gene can be associated with bona fide ADH.